(untitled) (World Economics and Finance Bulletin, 2026)
This article develops an organizational and economic criteria system for evaluating strategic management effectiveness in media business. Unlike traditional approaches that focus mainly on financial outcomes, the proposed framework treats media management effectiveness as a diagnostic construct shaped by managerial quality, economic efficiency, market position, innovation capacity and resource productivity. The study applies a weighted scoring logic, where each component is normalized on a 0–4 scale and interpreted through a strategic maturity matrix. The results show that economic efficiency and managerial quality are relatively strong dimensions, while innovation capacity remains the most sensitive zone requiring strategic intervention